Effect of Government Expenditures and Job Opportunities on Economic Growth and Poverty in Central Kalimantan Province - Sondang Nauly Hasibuan; Gundik Gohong; Misel Jaya (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2019)
This study aims to analyze the effect of government spending and employment opportunitieson economic growth and poverty in Central Kalimantan Province. The research method isquantitative by using secondary time series data from 2010-2016. Data is analyzed using pathanalysis. The results found that government expenditure had a significant effect on economicgrowth in Central Kalimantan Province, government expenditure does not have a significanteffect on poverty in Central Kalimantan Province, job opportunities have a significant effecton economic growth in Central Kalimantan Province, job opportunities have a significanteffect on poverty in Central Kalimantan Province, so the Prob (0.004). Economic growth hasa significant effect on the level of poverty in Central Kalimantan Province, so the Prob(0.001). Government expenditure does not have a significant effect on poverty levels througheconomic growth in Central Kalimantan Province, so Prob (-0.724). Job opportunities have asignificant effect on poverty levels through mediating economic growth in CentralKalimantan Province, so Prob (1,198).